Etika Komunikasi Levinas dalam Pengarusutamaan Gender di Lingkungan Perusahaan - Lia Rahayu Utami; Novia, Reni (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2025)
This research aims to examine the implementation of gender mainstreaming at PT Eagle Industry Indonesia through the ethical approach of Emmanuel Levinas, particularly the concept of the Other and the responsibility towards